A review of strategies and levels of community engagement in strengths-based and needs-based health communication interventions - Stover, Jesse; Avadhanula, Laxmisupriya; Sood, Suruchi (Frontiers in Public Health, 2024)
Background: Community engagement is key in health communication interventions that seek to incorporate community voices in their planning and implementation. Understanding what approaches and strategies are currently being used can help tailor programs in different social and cultural contexts. This review explores needs-based and strengths-based approaches and consensus and conflict strategies in community-based global health communications programs. Our objective is to examine the current state of the field, outline lessons learned, and identify gaps in existing programming to help guide future interventions. Methods: PubMed and Web of Science were searched for articles published between 2010 and 2023. Studies were included if they described a community-based health communication intervention and an ongoing or completed implementation. Interventions were coded then categorized according to their level of community engagement and as single, hybrid, or complex, depending upon the number of approaches and strategies used. Results: The search yielded 678 results and 42 were included in the final review and analysis. A vast majority 34 (81.0%) interventions utilized a needs-based approach and 24 (57.1%) utilized a strengths-based approach. Consensus as a strategy was utilized in 38 (90.5%) of the manuscripts and 9 (21.4%) implemented a conflict strategy. Interventions that combined approaches and strategies were more likely to leverage a higher level of community engagement. Conclusion: These results showcase the complicated nature of global health communication program planning and implementation. There is a lack of interventions that use conflict as a strategy to empower communities to act on their own behalf, even when at odds with existing power structures. Complex interventions that include all approaches and strategies demonstrate the potential for global health communication interventions to be at the cutting edge of public health practice.